ADMINISTRATIVE AND JURISDICTION ACTIVITY OF SECURITY SERVICES OF UKRAINE: THEORY AND PRACTICE OF LEGAL REGULATION - Калюжний, Ростислав Андрійович; Шапенко, Людмила Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Review of the monograph by A.M. Blahodarnoho "Conceptual principles of legal regulation of administrative and jurisdictional activities of the Security Service of Ukraine."The reviewed monograph comprehensively examines the theory and practice of legal regulation of administrative and jurisdictional activities of the Security Service of Ukraine; the legal status of the specified bodies as subjects of administrative and jurisdictional activity is defined; the functions and principles of the specified activity are characterized; the classification is offered and features of administrative-jurisdictional proceedings carried out by state security bodies are revealed. Proposals for amendments to the current legislation aimed at improving the legal regulation of administrative and jurisdictional activities of the Security Service of Ukraine are provided.The reviewers concluded that the presented monograph is a complete scientific work, and its provisions can be used for further study of the organization and implementation of administrative and jurisdictional activities, improvement of current legislation and practice of its application by law enforcement officers, as well as in teaching disciplines. basics of operational and service activities of the Security Service of Ukraine.